The global struggle for sexual and reproductive health and rights: Countering their undermining in international forums - Franziska Schwebel; Michael Bayerlein; Pedro A. Villarreal (Stiftung Wissenschaft und Politik (SWP), 2024)
In numerous countries, more restrictive regulations on abortions have recently led to a weakening of sexual and reproductive health and rights (SRHR). These legislative developments at the national level are reflected in the discussions at international forums, as they hinge upon human rights standards and access to health services. Although Germany has always advocated for the broad protection of SRHR, it is striking that the German government is not very active in international forums when it comes to addressing the content of this set of rights. This approach of diplomatic restraint carries the risk of providing those who oppose a broad interpretation of SRHR - be they governments, organisations or individuals - with a means to undermine the concept. If the German government wants to pursue its international commitment to human rights and individual freedoms in global health as well, more active advocacy is required.
Keywords: 320; sexual and reproductive health and rights (SRHR); human rights; individual freedoms; WHO Executive Board; Geneva Consensus Declaration; abortion; LGBTIQ+; EU health commissioner; Olivér Várhelyi; gender inclusivity